ECONOMIC AND ECOLOGICAL ASPECTS OF THE USE OF NEW CRYOGENIC AVIATION FUELS - Kraev, Vyacheslav; Tikhonov, Alexey; Kuzmina-Merlino, Irina (Journal of Applied Engineering Science, 2022)
Until recently, the high rates of aircraft engine engineering’s development were ensured by the technological solutions improvement and the desire to approximate as much as possible the ideal thermodynamic cycle of turbojet engines. The traditional fuel for turbojet engines is an aviation kerosene – Jet-A fuel group and their regional analogies. The traditional way of aircraft engines efficiency increasing is a raising of a temperature in front of the high-pressure turbine. New alloys and technologies allow to increase the aircraft engines efficiency to a certain level. Raising the temperature in the combustion chamber by 50 degrees increases the efficiency, which leads to a 5% reduction in fuel consumption. However, this approach is technology limited and does not provide innovative solutions. The aircraft engine engineering’s development tempo in the 21st century continues to accelerate. The main driver of such processes in recent years is the tightening of economic and environmental requirements. Many aircraft manufacturers are actively looking for ways to reach a new qualitative level in terms of turbojet engines economic efficiency and meeting strict environmental requirements. The paper considers the feasibility of using new cryogenic fuels in aircraft turbojet engines, and possible ways for aircraft industry successful development.
Keywords: aviation industry, economic and ecological aspects, aircraft engines, aviation fuels